41 Diagnosing Bone Metastases in Breast Cancer – CT Vs Nuclear Medicine Bone Scan. (4th May 2021) - Hiddema, L; Muthusami, A; Brookes, P; Green, M; Kasana, I
Abstract: Introduction: Guidelines advise use of CT or MRI to detect bone metastasis in breast cancer. Bone-scintigraphy (BS) is not routinely indicated. However, our patients with new node positive breast cancer, or symptoms suggestive of bone metastases, undergo both CT and BS. We aimed to evaluate discrepancies between CT and BS results, and assess whether CT is more accurate in diagnosing bone metastases in breast cancer patients. Method: Over a 2-year period, breast cancer patients who underwent CT and BS within 28 days of each other, were included. Scan reports were reviewed, and where unclear, MDT outcome was consulted. Results: Of 149 patients, 15 (10.1%) had discordant scan results. Where CT was negative, and BS suspicious (n = 6) or positive (n = 3), patients were either found to have visceral metastases on CT, BS was found to be a false positive, or MDT concluded there were no bone metastases. Where CT was positive and BS negative (n = 4), MDT confirmed metastases. Conclusions: CT is as good as BS in demonstrating bone metastases, and also detects visceral metastases. Using CT only would reduce radiation exposure, costs, and burden on service provision. We advise a change in local policy, with CT scan as the primary investigation for breast cancer staging.